Pengaruh Pembelajaran Berbasis Digital Berbantuan Wordwall Terhadap Minat dan Hasil Belajar IPS Siswa Kelas V SD Gugus 1 Kecamatan Bontomarannu Kabupaten Gowa - Nurjannah, Nurjannah; Nawir, Muhammad; Idawati, Idawati (LPPM Institut Pendidikan Nusantara Global, 2025)
This work aims to determine the relationship between Wordwall learning and the interests and learning outcomes of class V SD Gugus 1, Bontomarannu District, Gowa Regency. The study used a quantitative approach with Nonequivalent Control Group Design. The sample consisted of 50 students with purposive sampling, consisting of an experimental class (using Wordwall) and a control class (using conventional methods). Data were obtained through questionnaires, while the results were obtained from pretest and posttest tests. Data analysis was carried out using descriptive and inferential statistics, including normality, homogeneity, t-test, ANOVA, and MANOVA tests. The results showed that digital-based learning with the help of Wordwall had a significant effect on increasing students' interests and learning outcomes. The average score of students' interests and learning outcomes in the experimental class was higher than in the control class. The MANOVA test showed significance at a value of 0.001 (<0.05), which confirmed that Wordwall was effective in increasing students' interests and learning outcomes in social studies.